Identification of QTLs for 14 Agronomically Important Traits in Setaria italica Based on SNPs Generated from High-Throughput Sequencing. Issue 5 (1st May 2017) - Zhang, Kai; Fan, Guangyu; Zhang, Xinxin; Zhao, Fang; Wei, Wei; Du, Guohua; Feng, Xiaolei; Wang, Xiaoming; Wang, Feng; Song, Guoliang; Zou, Hongfeng; Zhang, Xiaolei; et al.
Abstract: Foxtail millet ( Setaria italica ) is an important crop possessing C4 photosynthesis capability. The S. italica genome was de novo sequenced in 2012, but the sequence lacked high-density genetic maps with agronomic and yield trait linkages. In the present study, we resequenced a foxtail millet population of 439 recombinant inbred lines (RILs) and developed high-resolution bin map and high-density SNP markers, which could provide an effective approach for gene identification. A total of 59 QTL for 14 agronomic traits in plants grown under long- and short-day photoperiods were identified. The phenotypic variation explained ranged from 4.9 to 43.94%. In addition, we suggested that there may be segregation distortion on chromosome 6 that is significantly distorted toward Zhang gu. The newly identified QTL will provide a platform for sequence-based research on the S. italica genome, and for molecular marker-assisted breeding.